Pembelajaran Keluarga Terhadap Keagamaan Anak Pada Usia Remaja - Sayed Sayed (IJoIS: Indonesian Journal of Islamic Studies, 2020)
The results of this study indicate that Family Empowerment Against Religious Children in the Village Black Water Sea Sadu District Tanjung Jabung East Regency has not been optimal because the Family Empowerment Against Religious Children in the Village Black Sea Water Sadu District East Tanjung Jabung Regency is not biased in saying good, because the parents although it has not been biased to exemplify to the adolescent child teenagers. The character of teenager in Air Hitam Laut Village, Sadu Sub-District, Tanjung Jabung Timur Regency, tends to be negative due to the weak communication and attention given by the head of RT and also the parents of the community in developing the teen characters towards the better, as well as the poor attention of parents to the religious behavior of parents to their children. The religious behavior of parents in improving the character of adolescents in the Village of Black Sea Black Sadu District Tanjung Jabung East Regency is by way of exemplifying good religious behavior in adolescents, parents also always advise adolescents to never leave prayers five times, some parents also put his son to an Islamic religious institution such as Mts Ataupun MA, and parents also send their teenage children to follow religious activities in the mosque or in the village of Air Hitam Laut, Sadu District, Tanjung Jabung Timur Regency. Based on the research findings, the implications of this research are: 1) Chairman of Rt to give more attention to the community and always support the existing religious activities in the neighborhood RT 07) to parents in order to develop better teenage character toward the better. As a parent must also bias exemplifies good behavior of goodness to the teenager, so teenagers bias ebih character and not trapped in a negative association.